Tommaso Greco's proposal about La legge della fiducia. Alle radici del diritto - Asís, Rafael de (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This article is part of the monographic section "Derecho y confianza”La legge della fiducia. Alle radici del diritto, is a proposal for understanding the Law and, at the same time, an invitation to reflect on its meaning and sense. These brief reflections address some of the questions on which the book invites reflection and raise some of the doubts raised by Tommaso Greco’s proposal.
Keywords: trust; duty; security; compliance